(untitled) (Biological Sciences - PJSIR, 2020)
A field study was conducted to investigate the effect of different N fertilizer sources (urea, nitrophos, ammonium sulphate and calcium ammonium nitrate) on the productivity of wheat (var. Inqlab) in naturally salt-affected soil (pH = 8.79; ECe = 6.46; Sandy loam). A significant difference was observed in wheat grain and straw yield with the application of different N sources. Maximum wheat grain and straw yields (3203 and 3489 kg/ha, respectively) were recorded when ammonium sulphate was applied. Various N sources followed the order: Ammonium sulphate > urea > calcium ammonium nitrate and/or nitrophos. Comparatively higher N uptake by wheat (117.26 and 114.00 kg/ha) was observed with Ammonium sulphate and urea application, respectively. Similarly, maximum N recovery was observed with both these N sources followed by nitrophos, and calcium ammonium nitrate. However, the highest physiological efficiency (14.29 kg/kg fertilizer applied) was noted with the application of ammonium sulphate.